'He would by no means risque his Reputation': patient and doctor shame in Daniel Turner's De Morbis Cutaneis (1714) and Syphilis (1717). Issue 4 (17th January 2017) - Cock, Emily
Abstract : This article offers a historical corollary to the examination of shame in medical practice by considering the negotiation of shame in the treatment of a stigmatised disease at a time in which surgeons themselves occupied a highly ambivalent social position. It will focus on case studies provided by Daniel Turner (1667–1741), prominent surgeon and later member of the College of Physicians, in his textbooks De Morbis Cutaneis. A Treatise of Diseases Incident to the Skin (1714) and Syphilis. A Practical Dissertation on the Venereal Disease (1717). Turner demonstrates an awareness of the precarious position of both the surgeon and the syphilitic, and devotes significant portions of his text to advising the trainee surgeon on how to manage patients' reticence over disclosure of symptoms, expectations for cure and impudence towards medical authority. In turn, the trainee must manage his own reputation as a moral and medical authority who can treat all distempers, yet without condoning or facilitating the shameful behaviours associated with a sexual disease. Furthermore, shaming plays a key role in enabling Turner to fashion an ideal patient whose successful cure will both respond to and build the surgeon's medical authority and that of the medical field in general.